Aportación a las letras quiteñas: el testamento del Doctor Cristóbal de Arvildo - Viforcos Marinas, María Isabel (Estudios humanísticos. Geografía, historia y arte, 1997)
This article is centred on analyzing the will of Dr. Cristóbal de Arvildo, a poet and orator who lived in Quito in the middle years of the seventeenth century. Although highly rated by his contemporaries, he is almost unknown today. The work consists essentially of two parts. The first undertakes an analysis of the which was drawn up on 18 june 1667, and corresponds basically to the normal pattern used by clergymen in Quito during this century. The second provides the principal data for a biographical sketch of this figure, covering his birth and family environment, his financial situation, his social relationships, and even his mentality.